Pengaruh Modal Sosial Dan Orientasi Kewirausahaan Terhadap Strategi Harga Pada Umkm - Laoli, Alex Putra Berkat; Zebua, Dermawan (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This research aims to analyze the influence of social capital and entrepreneurial orientation on pricing strategies among MSME actors. The research method employed is a quantitative approach using multiple linear regression analysis to test the relationships between variables. The results indicate that social capital plays a crucial role in determining price flexibility, while entrepreneurial orientation drives innovation in competitive pricing. In conclusion, the integration of strong social networks and risk-taking behavior is vital for business sustainability in dynamic markets. This abstract provides a general description without the use of citations or unfamiliar technical terms.